2021
DOI: 10.1002/mrm.28700
|View full text |Cite
|
Sign up to set email alerts
|

Deuterated water imaging of the rat brain following metabolism of [2H7]glucose

Abstract: Purpose: To determine whether deuterated water (HDO) generated from the metabolism of [ 2 H 7 ]glucose is a sensitive biomarker of cerebral glycolysis and oxidative flux. Methods: A bolus of [ 2 H 7 ]glucose was injected through the tail vein at 1.95 g/kg into Sprague-Dawley rats. A 2 H surface coil was placed on top of the head to record 2 H spectra of the brain every 1.3 minutes to measure glucose uptake and metabolism to HDO, lactate, and glutamate/glutamine. A two-point Dixon method based on a gradient-ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Furthermore, a recent publication compered DMI and HP [1- 13 C] pyruvate in imaging of cerebral metabolism, showing that they are both feasible methods at 4.7 T [ 61 ]. An alternate approach, described recently in Mahar et al, was to assess cerebral glucose metabolism by administering [ 2 H 7 ] glucose by looking at the HDO as the metabolic product, bypassing the need for lower resonance products such as lactate and Glx and showing that HDO can indeed serve as a biomarker of [ 2 H 7 ] glucose, lactate, and Glx metabolism [ 99 ]. Riis-Vestergaard et al reported the effect of temperature on metabolically active brown adipose tissue.…”
Section: Probes For Dmimentioning
confidence: 99%
“…Furthermore, a recent publication compered DMI and HP [1- 13 C] pyruvate in imaging of cerebral metabolism, showing that they are both feasible methods at 4.7 T [ 61 ]. An alternate approach, described recently in Mahar et al, was to assess cerebral glucose metabolism by administering [ 2 H 7 ] glucose by looking at the HDO as the metabolic product, bypassing the need for lower resonance products such as lactate and Glx and showing that HDO can indeed serve as a biomarker of [ 2 H 7 ] glucose, lactate, and Glx metabolism [ 99 ]. Riis-Vestergaard et al reported the effect of temperature on metabolically active brown adipose tissue.…”
Section: Probes For Dmimentioning
confidence: 99%
“…A bolus of [6,6′- 2 H 2 ] Glc in mice anesthetized by isoflurane resulted in the transfer of the 2 H labeling to the glutamate–glutamine pool, water pool, and lactate pool as previously reported in the rat brain [ 17 , 18 , 39 ]. Interestingly, when a similar bolus was infused into mice anesthetized by a combination of medetomidine and isoflurane, no labeling in the lactate pool could be detected in the mouse brain ( Figure 1 b,e and Figure 2 a,b).…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, the sum analysis of the metabolites labeled 1 hour post bolus of [6,6′- 2 H 2 ] Glc showed labeling in the Lac pool only in the ISO group, as well as a significantly higher HDO labeling in this group. After 1 hour from [6,6′- 2 H 2 ] Glc bolus, the metabolites detected by 2 H MRS are not only a product of cerebral utilization of [6,6′- 2 H 2 ] Glc, but also a consequence of the exchange with labeled blood Lac and water resulting from metabolism of Glc in peripheral organs [ 39 ]. Thus, the observed significant differences in 2 H labeling of Lac and water imply a global effect of the anesthesia on the animal’s metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the intravenous or intraperitoneal administration of deuterated glucose (such as [6,6′‐ 2 H 2 ] glucose or [ 2 H 7 ] glucose) in animal models or human subjects leads to the production of its downstream metabolites over time which can be captured in dynamic or steady‐state measurements, providing insights into metabolic flux through disease‐related metabolic pathways. Though DMI has served as a promising reporter of glucose metabolism in the normal brain and liver as well as in brain, liver, and lymphatic tumors, 4,6–12 none of the studies explore the possibility of this technique to study pancreatic cancer which remains a major challenge for early detection and treatment 13 . Much effort has been devoted to develop diagnostic methods, such as CT, FDG‐PET, 1 H MRI, for targeting and imaging pancreatic tumors, although imaging contrast is still difficult to achieve.…”
mentioning
confidence: 99%